Language choices and mental health: Black South African medical doctors' view on teaching indigenous African languages to children - Kaaka, Mmaphuti Dorothy (University of the Witwatersrand, Johannesburg, 2023)
Background: In a rapidly globalising world, safeguarding cultural heritage and indigenous languages is crucial. This study examined the views of black South African medical practitioners on teaching indigenous African languages to children at home amid challenges posed by English being the main language of teaching in formal education. Aim: We explored the perceptions of black South African doctors working in psychiatry regarding teaching indigenous African languages to children and investigated their reasons and the perceived impact of these choices on children's mental health. Setting: Urban-dwelling black South African indigenous language-speaking doctors who worked at community psychiatry clinics near Johannesburg, South Africa, were interviewed. Methods: A qualitative, descriptive research design was used. One-on-one interviews of twelve purposively sampled participants were held and transcribed. The data was analysed thematically. Results: Five themes were generated. Participants emphasised teaching their children African indigenous languages for cultural preservation purposes. They held that formal English-medium education hindered fluency in indigenous languages when spoken by children. Parents reported anxiety during visits to rural parts of South Africa due to the English-speaking child's inability to speak the parent's indigenous language with other rural-based black people. Perceived ostracism by other black people and the impact thereof on their children's mental health was a concern. The future of African indigenous languages was feared to be bleak. Conclusion and contribution: In conclusion, this research demonstrates that black South African doctors working in psychiatry facilities value teaching indigenous African languages to children to preserve culture. It highlights concerns about the negative impact of English-medium education on indigenous African language fluency of children and the potential mental health consequences of social isolation from other black people due to language barriers. The study suggests more inclusive education and efforts to revive indigenous languages at home to mitigate these concerns.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Psychiatry, to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023
Keywords: Indigenous African languages; Vernacular; Language loss; Black South African medical doctor; Psychiatry; Children’s mental health; Social isolation; Anxiety; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education